Challenges and opportunities in agriculture for African youth - Moitui, Joash N. (Technical Centre for Agricultural and Rural Cooperation, 2019)
This brief explores the challenges and opportunities facing young people trying to enter the agricultural and agribusiness sector. It focuses on actions that governments and other development actors can take to make the sector more attractive to young people, with an emphasis on those that can increase productivity, strengthen the value chains and increase the participation of young people in policy dialogue.